Clinical pathophysiology of proteinuria - A. Gozhenko; A. Haminich; O. Vityukov (Journal of Education, Health and Sport)
Proteinuria is the most important classical criterion of renal pathology, and its main characteristic is considered to be the quantitative degree of protein excretion. The latter in most patients determines the degree of nephron damage, the chronicity of the process in the kidneys, the prognosis of nephrological disease and the term of development of renal failure. Therefore, the clinical significance of proteinuria is quite significant, and consists in the timely detection and adequate treatment of proteinuria. The aim of the study was to determine and compare proteinuria under conditions of daily and induced salt diuresis. Materials and methods. 20 patients with proteinuria were selected for the study, 10 patients with diabetes mellitus and 10 patients with hypertension, who were inpatients. The age of the patients ranged from 31 to 59 years. Conclusions. 1. With water-salt loading, glomerular filtration rate, diuresis and total proteinuria increase. 2. Determination of latent proteinuria is a more informative indicator of kidney damage than comparing protein excretion during spontaneous, daily and induced water-salt diuresis. 3. The ratio of specific proteinuria to excretion of mmol creatinine or 1 ml of glomerular filtrate in % during salt loading compared to spontaneous daily diuresis is an important criterion for the degree of kidney damage. 4. Specific proteinuria is a marker of nephron damage, since it shows the true amount of protein that the nephron loses under conditions of its functional provocation; therefore, the study of specific proteinuria is quite relevant in the preclinical stages of kidney damage and can serve as one of the screening tests in risk groups with urinary system pathology.